2014
DOI: 10.1007/s10461-014-0792-1
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Interpersonal Characteristics that Influence Male-Dominated Sexual Decision-Making and Inconsistent Condom Use Among Married HIV Serodiscordant Couples in Gujarat, India: Results from the Positive Jeevan Saathi Study

Abstract: Approximately 40 % of new infections occur among married women. No studies have examined the factors that may contribute to HIV transmission among HIV-negative wives in HIV serodiscordant relationships in Gujarat, India. In 2010, a cross-sectional survey with 185 HIV serodiscordant, married couples (i.e. 185 HIV-positive husbands and their 185 HIV-negative wives) in Gujarat was conducted. Socio-demographic, individual, and interpersonal characteristics of HIV-positive husbands and their HIV negative wives were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Furthermore, a study of female sex workers in Ethiopia found that, work related violence was a contributing factor to unprotected sex among young people, thus facilitating the spread of sexually transmitted infections (Mooney et al, 2013). In another study, Patel et al (2014) reported that 10% of couples in India use condoms inconsistently in the past three months and the likelihood of inconsistent condom use was higher among partners who have suffered violence. Wealth was also given considerable attention in the study as a contributing factor toward inconsistent condom use.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study of female sex workers in Ethiopia found that, work related violence was a contributing factor to unprotected sex among young people, thus facilitating the spread of sexually transmitted infections (Mooney et al, 2013). In another study, Patel et al (2014) reported that 10% of couples in India use condoms inconsistently in the past three months and the likelihood of inconsistent condom use was higher among partners who have suffered violence. Wealth was also given considerable attention in the study as a contributing factor toward inconsistent condom use.…”
Section: Discussionmentioning
confidence: 99%
“…While the causal mechanisms underlying these associations are not fully understood, it is clear that FI compromises women’s ability to negotiate safer sex practices when they are dependent on men for food and other resources. FI may also exacerbate gender-based imbalances in relationship power that can increase sexual risk by enhancing male control and decision-making dominance in sexual relationships, including the timing and frequency of sex (Patel et al, 2014; Shannon et al, 2012). Women’s low sexual relationship power has also been associated with less condom use (Campbell et al, 2009; Pettifor, Measham, Rees, & Padian, 2004; Pulerwitz, Amaro, De Jong, Gortmaker, & Rudd, 2002) and with physical violence and forced sex (Muldoon, Deering, Feng, Shoveller, & Shannon, 2015; Pulerwitz, Gortmaker, & De Jong, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these impacts, including rejection by family, abuse by husband and in-laws, selective maltreatment in pregnancy by healthcare professionals especially when HIV status is known, HIV testing by coercion, sterilisation and abortion have not been reported as HIV impacts on men and other KAPs (26)(27)(28). Rejection and abuse against WLHIV by husbands and in-laws, for example, seem to be the consequences of the patriarchal system or sociocultural norms and values prevailing within societies and communities in many developing countries, that promote male or husbands' domination over women or wives' submission to husbands or male partners (45)(46)(47)(48)(49). Being infected with HIV also causes negative self-stigma among WLHIV, such as paranoia about people's negative reactions to their HIV status, fear of HIV status being recognised and spread out by other people and fear of rejection, and self-isolation.…”
Section: An Explanatory Conceptual Model For the Impacts Of Hiv On Wlmentioning
confidence: 99%